KONSTRUKSI PERTANGGUNG JAWABAN PIDANA LAKI-LAKI ATAS PERBUATAN MENELANTARKAN PEREMPUAN DAN ANAK DI LUAR KAWIN - Nahdiya Sabrina (University of Merdeka Malang, 2016)
The act of a man releasing responsibility for a woman’s pregnancy outside of marriage is an act that deemeddeplorable in society, and of course, bring harm to women and children. But until this moment there is no rulethat can be used to ensure the perpetrator or to force him to account for the act. By not regulating this act thestate would surely let this act continue so that more and more children become victims. Whereas this act iscontrary to the mandate of law no. 35 the year 2014 regarding the amendment to the law no 23 the year 2002 on childprotection.